PRAGMATIC REPRESENTATION OF EMOTIONAL CONCEPTS IN CONTEMPORARY AMERICAN POETRY: THE CASE OF LOUISE GLÜCK - Islomova Dilnoza Barkamol qizi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Contemporary American poetry has been marked by a persistent effort to negotiate the boundaries between personal experience, cultural memory, and communicative function. Among its most notable voices, Louise Glück stands out for her ability to transform emotional concepts into pragmatic structures that serve not only aesthetic but also cognitive and interpersonal purposes. Her poems demonstrate how emotions are represented through language not merely as subjective states but as tools of interaction and interpretation. By embedding private feelings in discursive strategies that resonate across diverse audiences, Glück achieves a balance between intimacy and universality. This study explores the pragmatic dimensions of her work, examining how metaphor, silence, direct address, and mythological reference enable emotions to act as communicative acts rather than isolated sensations.